Inpatient Insulin Pen Implementation, Waste, and Potential Cost Savings: A Community Hospital Experience. (July 2021) - Najmi, Urooj; Haque, Waqas Zia; Ansari, Umair; Yemane, Eyerusalem; Alexander, Lee Ann; Lee, Christina; Demidowich, Andrew P.; Motevalli, Mahsa; Mackay, Periwinkle; Tucker, Cynthia; Notobartolo, Cindy; Sartippour, Poroshat; et al.
Background: Insulin pen injectors ("pens") are intended to facilitate a patient's self-administration of insulin and can be used in hospitalized patients as a learning opportunity. Unnecessary or duplicate dispensation of insulin pens is associated with increased healthcare costs. Methods: Inpatient dispensation of insulin pens in a 240-bed community hospital between July 2018 and July 2019 was analyzed. We calculated the percentage of insulin pens unnecessarily dispensed for patients who had the same type of insulin pen assigned. The estimated cost of insulin pen waste was calculated. A pharmacist-led task force group implemented hospital-wide awareness and collaborated with hospital leadership to define goals and interventions. Results: 9516 insulin pens were dispensed to 3121 patients. Of the pens dispensed, 6451 (68%) were insulin aspart and 3065 (32%) were glargine. Among patients on insulin aspart, an average of 2.2 aspart pens was dispensed per patient, but only an estimated 1.2 pens/patient were deemed necessary. Similarly, for inpatients prescribed glargine, an average of 2.1 pens/patient was dispensed, but only 1.3 pens/patient were necessary. A number of gaps were identified and interventions were undertaken to reduce insulin pen waste, which resulted in a significant decrease in both aspart (p = 0.0002) and glargine (p = 0.0005) pens/patient over time. Reductions in pen waste resulted in an estimated cost savings of 66 261 per year. Conclusions: In a community hospital setting, identification of causes leading to unnecessary insulin dispensation and implementation of hospital-wide staff education led to change in insulin pen dispensation practice. These changes translated into considerable cost savings and facilitated diabetes self-management education.